IMPLEMENTASI SIMPLE ADDITIVE WEIGHTING (SAW) PADA SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMAAN MAHASISWA BARU POLITEKNIK SERUYAN - Pratiwi, Evi Lestari; Pratama, Ramadhani Noor; Pratomo, Adi (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
The determination of new student admissions is a crucial process for every higher education institution. To enhance efficiency and objectivity in decision-making, the implementation of the Simple Additive Weighting (SAW) method has been carried out in the decision support system of Politeknik Seruyan. The SAW method is utilized to calculate and assign weights to relevant criteria in the selection of new prospective students.This research elaborates on the implementation process of SAW within the decision support system of Politeknik Seruyan. Data pertaining to prospective students, including entrance exam scores, academic achievements, and other relevant factors, are collected and processed using the SAW method. The outcomes of these calculations provide rankings for prospective students based on their degree of conformity with the criteria established by the polytechnic. The results of this research demonstrate that the use of the SAW method in the process of selecting new student admissions has improved efficiency, objectivity, and transparency in decision-making. With the existence of a SAW-based decision support system, Politeknik Seruyan can make more accurate decisions in accepting new students in accordance with the criteria and educational objectives set by the institution. The implementation of the SAW method in the decision support system contributes positively to enhancing the quality of new student admissions at Politeknik Seruyan.